Depression among parents of disabled children - Millaku, Jetmira; Kraja-Bardhi, Eglantina (International Journal of Innovative Research and Scientific Studies, 2023)
The purpose of this study was to measure the scale of depression among parents of disabled children. The study focused on understanding the relationship between the financial state of parents and depression, gender differences and the impact of parents’ age on depression. In this research, 74 parents of disabled children participated including 37 mothers and 37 fathers. The research was conducted in the Peja region. The Beck's depression questionnaire was used. There were additional demographic questions in the questionnaire including one question about children’s diagnoses, one about parents' education and one about children's age. The SPSS 16 version was used to analyze the data. Analyses done in this research are: descriptive analyses, independent t-tests and Pearson correlations. The results have shown that mothers are more depressed than fathers. Another factor that impacts parents’ depression is their financial state where the results have shown that families with lower income tend to have more depression compared to others who have a higher income. Moreover, based on the results of the study, it was found that parents' age does not correlate with depression and parents of children with autism and mental development delays have higher scales of depression.